2019
DOI: 10.1016/j.amsu.2019.09.001
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of 30-day outcomes following mitral valve repair

Abstract: IntroductionMitral valve repair has been established as the preferred treatment option in the management of degenerative mitral valve disease. Compared with other surgical treatment options, mitral valve repair is associated with increased survival and decreased rates of both complications and reoperations. However, among patients undergoing mitral valve repair, little is known about the predictors of postoperative outcomes. The purpose of this study is to identify preoperative patient risk factors associated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 23 publications
1
2
0
Order By: Relevance
“…Advanced age and NYHA class ≥III have been shown to increase peri-operative mortality of valve surgery. (26,27,29) Our study did not show age having a direct effect on peri-operative mortality but confirmed that NYHA class ≥III is an independent risk factor for mortality, likely due to more patients in our study being younger than 60 years and a relatively small sample size. We also found that LVEF <35% was a strong predictor of mortality, confirming the importance of pre-operative echocardiography and functional assessment of the patient.…”
Section: Discussionsupporting
confidence: 65%
“…Advanced age and NYHA class ≥III have been shown to increase peri-operative mortality of valve surgery. (26,27,29) Our study did not show age having a direct effect on peri-operative mortality but confirmed that NYHA class ≥III is an independent risk factor for mortality, likely due to more patients in our study being younger than 60 years and a relatively small sample size. We also found that LVEF <35% was a strong predictor of mortality, confirming the importance of pre-operative echocardiography and functional assessment of the patient.…”
Section: Discussionsupporting
confidence: 65%
“…Atrial fibrillation increases the risk of death in patients undergoing MV surgery [13]. In the Reisman et al [14] study, preoperative hematocrit was a significant predictor of short-term mortality after MR repair. Heikinnen et al [15] observed that the New York Heart Association (NYHA) classification, patient age, and history of prior cardiac surgery on multivariate analysis were significantly associated with short-term mortality in patients after MV repair.…”
Section: Discussionmentioning
confidence: 98%
“…A meta-analysis of 22 studies and 114,277 patients showed a HR of 2.74 (95% CI 2.32-3.24) for 30-d or in-hospital mortality after cardiac surgery in anaemic patients [24]. In a study on possible predictors for 30-d mortality after mitral valve replacement, the only independent risk factor was haematocrit level (p ¼ .017) [25]. These findings are in agreement with those of our study, in which reduced haemoglobin was an independent risk factor with a 3.4-fold HR for 30-d mortality after cardiac surgery.…”
Section: Discussionmentioning
confidence: 99%